Physical and Electrochemical Properties of Soluble 3,4-Ethylenedioxythiophene (EDOT)-Based Copolymers Synthesized via Direct (Hetero)Arylation Polymerization - Guo, Qiang; Zhang, Jincheng; Li, Xiaoyu; Gong, Heqi; Wu, Shuanghong; Li, Jie (Frontiers in Chemistry, 2021)
Over the past decades, π-conjugated polymers (CPs) have drawn more and more attention and been essential materials for applications in various organic electronic devices. Thereinto, conjugated polymers based on the 3,4-ethylenedioxythiophene (EDOT) backbone are among the high-performance materials. In order to investigate the structure–property relationships of EDOT-based polymers and further improve their electrochemical properties, a series of organic solvent–soluble EDOT-based alternative copolymers consisting of electron-rich fragments (fluorene P1, carbazole P2, and 3,4-alkoxythiophene P3) or electron-deficient moieties (benzotriazole P4 and thieno[3,4-c]pyrrole-4,6-dione P5) were synthesized via direct C–H (hetero)arylation polymerization (DHAP) in moderate to excellent yields (60–98%) with medium to high molecular weights (Mn = 3,100–94,000 Da). Owing to their various electronic and structural properties, different absorption spectra (λmax = 476, 380, 558, 563, and 603 nm) as well as different specific capacitances of 70, 68, 75, 51, and 25 F/g with 19, 10, 21, 26, and 69% of capacity retention after 1,000 cycles were observed for P1–P5, respectively. After careful study through multiple experimental measurements and theoretical calculation, appropriate electronic characteristics, small molecular conformation differences between different oxidative states, and well-ordered molecular stacking could improve the electrochemical performance of CPs.